A Study On Diners’ Opinion Towards Induction Of Service Robots In Gujarat Restaurants (PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: The rapid development of technology has allowed the restaurant sector to integrate a wide range of  technologies into service settings. Service robots can boost efficiency and food service revenues. This study examines  consumer approval of diner service robots. Objectives: (a) To analyse diners' views on restaurant robots, (b) To  know the effect of demographic considerations on robot introduction in restaurants and (c) To examines diners views  on prospects and difficulties that affect service robot attitudes. Methodology: An exploratory research design with  structured questionnaire was distributed to 362 participants among which 337 were suitable for the study. Purposive  sampling was used to obtain diner’s perspective of inducting service robots in restaurants at major cities of Gujarat  (Ahmedabad, Surat, Baroda, Gandhinagar & Rajkot). Data analysis was done on the basis of demographic profile and  frequency of visit to the restaurants by using SPSS 25.0. Results: Based on admissible Eigen values, the study derived  three criteria for diner acceptance of service robots that explained 72.28% of variance. Hypotheses showed age and  gender influenced service robot induction. Education did not affect service robot acceptance. The study suggests that  people's views on robots affect their views on restaurant robots. Conclusion: The study shows that service robots could  assist restaurants. It specifies service robots' study operations. Diner acceptance of service robots will give a theoretical  framework for other service industries in technological acceptance and consumer behavior.
Keywords: Artificial Intelligence; Diners; Innovativeness; Restaurants; Service Robots